Quantification of tumour-infiltrating immune cells through deconvolution of DNA methylation data in Ewing sarcomas - Patrizi, Sara; Vallese, Silvia; Pedace, Lucia; Nardini, Claudia; Stracuzzi, Alessandra; Barresi, Sabina; Giovannoni, Isabella; Abballe, Luana; Antonacci, Celeste; Russo, Ida; Di Giannatale, Angela; Alaggio, Rita; et al. (Frontiers in Epigenetics and Epigenomics, 2024)
Ewing Sarcomas (EWS, OMIM#612219) presents a major challenge in pediatric oncology due to its aggressive nature and poor prognosis, particularly in metastatic cases. Genetic fusions involving the EWSR1 gene and ETS family transcription factors are common in EWS, though other rarer fusions have also been identified. Current standard techniques like immunohistochemistry have failed to fully characterize the immune tumor microenvironment of EWS, hindering insights into tumor development and treatment strategies. Recent efforts apply gene expression datasets to quantify tumor-infiltrating immune cells in EWS. Similar deconvolution techniques can be also applied to DNA methylation (DNAm) arrays, which are much more stable compared to RNA-based methods. This study aims to characterize immune cell infiltration in EWS using DNAm array data. We collected 32 EWS samples from 32 consecutive patients referred to Bambino Gesù Children’s Hospital. DNAm analysis was performed by EPIC arrays; data loading, normalization, deconvolution and survival analysis were then performed in R programming environment. We observed a higher content of dendritic cells and longer overall survival in samples with EWSR1::FLI1 translocation compared to samples with rarer fusions. Moreover, T-memory lymphocytes and monocytes emerged as a significant predictor of overall survival. This study underscores the potential of DNAm arrays in providing robust insights into EWS immune profiles, offering a promising avenue for future research. Further investigations with larger cohorts are warranted to validate these findings and explore additional immune cell types influencing EWS outcomes.